Bridging Language Barriers in Law Enforcement: A Study on the English Language Needs of Indonesian Police Officers - Suharno, Suharno; Suryana, Deddy (FKIP Universitas Lampung, 2025)
Bridging Language Barriers in Law Enforcement: A Study on the English Language Needs of Indonesian Police Officers. Objective: Policemen more often communicate in English when dealing with non-nationals, cooperating internationally, or dealing with international crime in general. However, in Indonesia, where English is used as a foreign language and is not widely used in society, achieving working proficiency becomes a significant challenge. The present study addresses the English language learning needs of police officers working in operational duties and responsibilities within a district-level police unit in West Java Province, Indonesia. Method: Data was collected through a qualitative case study involving 30 rank-and-file officers. These three types of data were gathered via in-depth interviews, structured questionnaires, and workplace observations. This approach provided a full picture of the linguistic difficulties as well as the language required for the task. Findings: The Results indicate that, despite their low level of English proficiency, most officers acknowledge the language as fundamental for a significant portion of their work, including daily interactions with foreign visitors, writing reports to support cases involving foreign nationals, and situations requiring knowledge of legal and procedural terminology in cross-border contexts.. The needs analysis identifies three key areas for growth: oral skills for basic conversation and emergencies, reading and writing skills for writing police reports, and proficiency in English documentation, as well as an understanding of specialized legal vocabulary relevant to policing. Conclusion/Implications: As a result, an English for Specific Purposes, task-based, and contextualised training program is proposed based on these findings. This would enhance the officers’ performance in the field, improve public service quality, and bolster Indonesia’s engagement in international law enforcement networks. Keywords: english for specific purposes, law enforcement training, needs analysis, operational language skill, police communication.